The determinants of board size and composition: Evidence from the UK - Guest, Paul M. (Elsevier, 2008)
This paper examines the trends and determinants of board structure for a large sample of UK firms from 1981 to 2002. We extend the predominantly US based literature in a number of important ways. Firstly, a comparative analysis of the UK and US legal and institutional settings leads us to hypothesize that UK boards will play a weaker monitoring role and hence board structures will not be determined by monitoring related factors. Our evidence supports this conjecture, showing that board structure determinants differ in predictable ways across different institutional settings. Secondly, in contrast to recent US mandatory reforms, UK reforms have been voluntary. As such they provide an interesting comparison, being arguably more effective than a mandatory approach by allowing firms to choose board structures most appropriate for their own needs. Our results support this point of view. Although the UK reforms do have a significant impact on board structures, a large number of firms choose not to comply, and those that do appear to do so for strong economic reasons. The reforms also appear to reduce the ability of well performing CEOs to influence board structures.
Keywords: Board size; Board composition; UK; US; Corporate governance; Cadbury; Hampel